GEOMETRICAL MODELLING OF KINEMATICS OF ARTICULATED ROBOTIC ARM - Bastawade, Keval Suresh (IAES International Journal of Robotics and Automation (IJRA), 2020)
This paper presents a direct way of modeling the Kinematics of an Articulated Robotic Arm. The range for industrial application of this configuration is wide. Kinematics includes Forward Kinematics and inverse Kinematics. Forward kinematics refers to conversion of joint angles to end effectors position whereas Inverse Kinematics refers to conversion of world co-ordinates of end effector to joint angles of the Arm. The proposed method uses spherical co-ordinate system to model it?s both Forward and Inverse Kinematics. Using this model, path planning for different scenarios can be done. Implementation of different algorithms to evaluate effective path by either avoiding obstacles or by passing through intermediate path points is possible. End effector of Robotic Arm easily follows complex 3D space curves like Circular Helix and Conical Helix, etc. using this algorithm. The above-mentioned algorithm also has been tested in scenarios where real time inputs from user are used for robotic arm actuation using a custom designed software